2017
DOI: 10.1590/1678-7757-2016-0665
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer stem cells - properties and consequences

Abstract: Research on cancer stem cells (CSCs) has greatly increased in the field of medicine and pathology; however, some conceptual misunderstandings are still present among the public as well as within the general scientific community that is not yet familiar with the subject. The very first problem is the misinterpretation of CSCs as a synonym of their normal counterparts, the well-known stem cells (SCs). Particularly in Dentistry, another common mistake is the misinterpretation of oral CSCs as normal tooth-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
15

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 43 publications
0
31
0
15
Order By: Relevance
“…Accordingly, only cells of the oral mucosa epithelium with phenotypic characteristics of stem cells -for example, a capacity for self-renewal and survival -can undergo the genetic and epigenetic changes that prompt tumor development. In this new alternative model of oral carcinogenesis, oncogenically transformed stem cells, now called CSC, are responsible for the genesis, sustainable growth, and metastatic dissemination of OSCC [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, only cells of the oral mucosa epithelium with phenotypic characteristics of stem cells -for example, a capacity for self-renewal and survival -can undergo the genetic and epigenetic changes that prompt tumor development. In this new alternative model of oral carcinogenesis, oncogenically transformed stem cells, now called CSC, are responsible for the genesis, sustainable growth, and metastatic dissemination of OSCC [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The OM-SCs in the basal layer of the oral mucosa are the normal stem cells essential for maintaining the integrity of the oral mucosa. 21 Contact with the basement membrane is required to maintain basal keratinocyte stemness. The severity of the contact of OM-SCs with the basement membrane promotes their differentiation.…”
Section: Alterations In the Expression Pattern Of Om-scms In Osf Opmmentioning
confidence: 99%
“…Although the stem cells associated with cancer are quite similar to normal stem cells and express the same markers, certain unique characteristics, such as the loss of growth control, justify their separate designation as cancer stem cells (CSCs) or tumourinitiating cells. 21,23,24 Several studies have shown that CSCs play a crucial role in the growth, spread and recurrence of oral cancer. [25][26][27][28][29][30][31] CSCs in oral cancer demonstrate elevated expression levels of stem cell markers, such as Oct-4, SOX2, Nanog, Nestin, CK19, B-cellspecific Moloney murine leukaemia virus integration site 1 (Bmi-1), CD117 (c-kit), CD44 and CD133, and decreased expression levels of involucrin and CK-13.…”
Section: Alterations In the Expression Pattern Of Om-scms In Osf Opmmentioning
confidence: 99%
See 1 more Smart Citation
“…Figura 2 -Comparação entre origem, trajetória e atuação de SC e CSC no organismo humano. (A) SC: evidencia a origem embrionária e/ou em tecidos adultos, a capacidade de autorrenovação e a possibilidade de diferenciação in vitro em vários tipos de células; (B) CSC: é possível localizar a origem no tecido adulto, a transformação maligna, a capacidade de autorrenovação, proliferação e diferenciação, contribuindo para o desenvolvimento do câncer, inclusive na geração de metástases (Rodini et al, 2016).…”
Section: Células-tronco De Câncerunclassified